Aerobic Exercise Training Improves Calcium Handling and Cardiac Function in Rats with Heart Failure Resulting from Aortic Stenosis - da Silva, Vítor Loureiro [UNESP] (2023)
Aerobic exercise training (AET) has been used to manage heart disease. AET may totally or partially restore the activity and/or expression of proteins that regulate calcium (Ca2+) handling, optimize intracellular Ca2+ flow, and attenuate cardiac functional impairment in failing hearts. However, the literature presents conflicting data regarding the effects of AET on Ca2+ transit and cardiac function in rats with heart failure resulting from aortic stenosis (AoS). This study aimed to evaluate the impact of AET on Ca2+ handling and cardiac function in rats with heart failure due to AoS. Wistar rats were distributed into two groups: control (Sham; n = 61) and aortic stenosis (AoS; n = 44). After 18 weeks, the groups were redistributed into: non-exposed to exercise training (Sham, n = 28 and AoS, n = 22) and trained (Sham-ET, n = 33 and AoS-ET, n = 22) for 10 weeks. Treadmill exercise training was performed with a velocity equivalent to the lactate threshold. The cardiac function was analyzed by echocardiogram, isolated papillary muscles, and isolated cardiomyocytes. During assays of isolated papillary muscles and isolated cardiomyocytes, the Ca2+ concentrations were evaluated. The expression of regulatory proteins for diastolic Ca2+ was assessed via Western Blot. AET attenuated the diastolic dysfunction and improved the systolic function. AoS-ET animals presented an enhanced response to post-rest contraction and SERCA2a and L-type Ca2+ channel blockage compared to the AoS. Furthermore, AET was able to improve aspects of the mechanical function and the responsiveness of the myofilaments to the Ca2+ of the AoS-ET animals. AoS animals presented an alteration in the protein expression of SERCA2a and NCX, and AET restored SERCA2a and NCX levels near normal values. Therefore, AET increased SERCA2a activity and myofilament responsiveness to Ca2+ and improved the cellular Ca2+ influx mechanism, attenuating cardiac dysfunction at cellular, tissue, and chamber levels in animals with AoS and heart failure.